The Extent of Awareness of Cyberbullying Coping Strategies among Middle School Female Students (The International Journal for Scientific Research, 2025)
This research investigated how aware middle school female students are of coping strategies for cyberbullying. The study considered the rapid digital transformation and increased use of technology and social media in schools. Using a descriptive–analytical approach, we administered the Cyberbullying Coping Strategies Scale to 120 randomly selected middle school female students. The findings showed that these students had a high awareness of cyberbullying coping strategies. The overall mean score was 2.36 (SD = 0.75). Most items demonstrated high awareness, particularly regarding practical preventive strategies. However, students showed lower awareness of cognitive strategies such as self-directed learning and information seeking. The results indicated no statistically significant differences in awareness by grade level (α < 0.05). This demonstrates consistency and a unified understanding among students. Several recommendations were given integrate digital safety and cyberbullying prevention into school curricula and guidance activities; organize periodic awareness and training workshops on digital protection for students; and implement joint awareness campaigns involving both schools and families to promote responsible online behavior.
Keywords: Awareness; Cyberbullying; Cyberbullying Coping Strategies